Art Commission Pre Order System Based Web Bootstrap in Art Circle Dynamic Entry - Moses, Moses; Kusumawati, Arie (I-STATEMENT, 2018)
Art Circle Dynamic Entry is a profitable business engaged in the field of digital art both fan making, original art, and visual novel. How Art Circle Dynamic Entry works in marketing marketing art commisssion mostly using online media such as facebook and Deviant Art. This study aims to build an order pre order art commission system in Art Circle Dynamic Entry that facilitates customers and artists in art pre order. System development method used in this research is method with Prototype process model and programming language used is PHP and JavaScript with phpMyAdmin software and MySQL database. The result of this research is the art commission pre order system based on web bootstrap in art circle dynamic entry which able to process the order data quickly so as to facilitate the customer in art pre order.